Outcome of Pregnancy in Patients after Laparoscopic Assisted Metroplasty for Uterus Diadalphus - Anaheeta Israr, Zubaida Khanum Wazir, Noreen Tahir, Shermeen Kousar, (Pakistan Journal of Medical & Health Sciences, 2024)
One of the mullerian duct disorder is didelphic uterus in which the uterine horns and cervix are completely duplicated, with no connection between them. . Patients with a didelphic uterus have high rates of abortion, preterm delivery, and term delivery. The aim of the study was to determine the Outcome of pregnancy in patients after Laparoscopic assisted metroplasty for uterus diadalphus. Methodology: The current study was conducted at the department of Gyne & Obs in Abbottabad Medical complex and Gulnawaz Teaching Hospital Bannu from May 2023 to Oct 2023 after taking permission from the ethical board of the institute .A total of 30 women who had a history of two preterm deliveries or abortions (not related to immunologic, genetic, or hormonal factors) and a sonohysterographically diagnosed with didelphic uteri were included .. Before the procedure, all of the participants had diagnostic hysteroscopy and had laparoscopic metroplasty from the same surgeon. Every patient had a second-look hysteroscopy and laparoscopy. Three months later to assess the uterine cavity's compliance and potential for adhesion development. One month following the second-look laparoscopy, or four months following the first procedure, patients were instructed to try to conceive. In order to detect pregnancy, all patients were expected to be monitored for a minimum of 12 months. We documented the rate of pregnancy, live births, adhesion development, problems, and compliance of the uterine cavity. Data was entered to Microsoft excel and presented in table and graphs. Results: 26(86.66%) of the women treated were successful in becoming pregnant, while 4(13.33%) postponed conception. Nineteen individuals (63.33) experienced a term pregnancy with typical pregnancy and delivery results. Two premature deliveries occurred in the Delphic group, both of which had incompetent cervixes and occurred at 22 weeks of gestation, despite vaginal corsage having been performed at 14 weeks. Four (13.33%) of the women being treated decided to postpone conception for their own privacy. Conclusion: From this study we concluded that laparoscopic metroplasty is safe, feasible, and efficient therapy for women with didelphic uteri who have successive or preterm deliveries. Of course, to validate the satisfactory pregnancy outcomes, further long-term research with larger sample sizes is needed Keywords: Didelphic uterus, Metroplasty, Pregnancy outcome, Preterm delivery, Laparoscopy, Hysteroscopy, Uterine anomaly